Healthcare Workers' Mental Health and Work-Family Conflict: The Moderating Effect of Work-Family Conflict Self-Efficacy - Balogun, Anthony G; Adetunji, Adeola M; Uye, Emmanuel E (MultiTech Publisher, 2024)
Healthcare workers experience multifaceted mental health issues due to the nature of their work. Some studies have investigated predictors of mental health with varied results. In Akure, Ondo State, Nigeria, this study looked at the moderating effects of work-family conflict self-efficacy (WFCSC) on the association between work-family conflict and mental health among healthcare professionals. The study adopted cross-sectional survey design while purposive sampling technique was used to select three state hospitals in Akure metropolis. Three hypotheses were tested through the use of zero-order correlation and three-step hierarchical multiple regression analysis on data obtained from 201 healthcare workers using validated scales. All hypotheses were accepted at p < .05 level of significance. The result indicated that work-family conflict significantly predicted mental health among study participants. Also, the result revealed that WFCSE significantly predicted mental health among healthcare workers. Finally, the result showed that WFCSE significantly moderated the relationship between work-family conflict and mental health among healthcare workers). The study found that among study participants, WFCSE is a powerful predictor and modifier of mental health. Consequently, it is advised that management offer mental health support services to employees in order to lessen the detrimental impact that work-family conflict self-efficacy has on mental health outcomes.